Meningkatkan Kompetensi Pedagogik Guru dalam Pembelajaran Berbasis Multi Sumber melalui Model Pembelajaran IODE di MI Nurul Huda 2 Surodinawan Prajuritkulon Kota Mojokerto - Muhammad Ihwan (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
This research is motivated by (a) the number of teachers who consider books as the only source of learning so that they cannot apply multi-source based learning (b) there are still teachers who have not mastered the IODE learning model, (c) the number of teachers who are only competent in Special Learning Models but difficult to implement new learning models such as IODE, (d) not all teachers have the opportunity to attend KTSP training or training, and (e) the scarcity of MGMP Activities specifically addresses the IODE Learning Model, so that the IODE learning model still feels unfamiliar in MI Nurul Huda 2 Surodinawan Prariorkulon Mojokerto City. Intake, Organizing, Demonstration, and Disclosure (Express) students in receiving learning information is still lacking, this is indicated by the reluctance of students to learn Indonesian, work carelessly and less enthusiastic in learning, to overcome this, the writer needs to do a School of Action Research ( CAR). Realizing the symptoms or facts mentioned above, in this study the writer took the title "Improving Teacher's Pedagogical Competence in Multi-Source Based Learning through the IODE Learning Model in MI Nurul Huda 2 Surodinawan Praututkulon Mojokerto City. Each round consists of four stages, namely: design, activity and reflection and revised observation. The purpose of this study was the teacher at MI Nurul Huda 2 Surodinawan Praututkulon Mojokerto City The data were obtained in the form of observation sheets of learning activities results. Multi-Based Resources through the IODE Learning Model has a positive impact on Efforts to Enhance Student Learning Achievement, this can be seen from students' better understanding of the material delivered by the teacher (mastery learning increases from cycles I, II, and III) namely cycle I 36 , 59%, second cycle 75.61%, da n cycle III 100%. The research is: Learning Based on Various Sources through the IODE Learning Model has a positive influence that can improve student learning achievement as indicated by the average student response which states that students are interested and interested in the Many Source Based Learning through the IODE Learning Model so that they become motivated to learn.